The best course available : a personal account of the secret U.S.-Japan Okinawa reversion negotiations - Wakaizumi, Kei, 1930-1996 (University of Hawai'i Press, 2002)
"This volume affords a look at the sensitive issue of nuclear diplomacy between two critical Cold War allies, the United States and Japan, during the 1960s.